Fiestas Patrias Mexican Independence 1996 - Parade and Fiesta - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1996 Mexican Independence Day Parade and Fiesta, presented by the San Jose Chapter of the American GI Forum.